Active and passive confinement of shape modified low strength concrete columns using SMA and FRP systems. (1st November 2020) - Suhail, R.; Amato, G.; McCrum, D.P.
Abstract: Several existing studies on the confinement effectiveness of shape modified concrete columns have been conducted in the past, but the scope of these studies has mostly been limited to passive confinement. The effectiveness of the active confinement of shape modified concrete columns has not been investigated to date. Therefore, in this study, monotonic compression tests were conducted to: (1) investigate the active confinement of shape modified concrete columns; and (2) compare the effectiveness of actively confined shape modified specimen with passively confined analogous specimens. Active confinement in this study was achieved by heat-activated prestressing (HAP) of shape memory alloy (SMA) spirals and passive confinement using basalt fibre-reinforced polymer (BFRP), carbon fibre-reinforced polymer (CFRP) jackets and reused SMA wires without HAP. The performance of the specimens was evaluated in terms of strength, ductility and damage in the specimens. In view of the complex material behaviour of SMAs, this study also aimed to highlight the benefits and difficulties of using SMAs for active confinement in practical applications. The results from this study show that as compared to unconfined and passively confined shape modified specimens, actively confined shape modified specimens exhibited significantly higher ductility and higher residual strength at relatively large axial deformation.